Go get 'em! Elites, depoliticization and resistance in the Catalan independence bid. Issue 2 (17th February 2021) - Murillo, David
ABSTRACT: Exploring the role of elites in recent liberal democratic crises is emerging as one of the most important themes of our times. In this regard, the Catalan bid or independence in autumn 2017 remains a puzzling example of a foreseeable crisis that produced a dramatic institutional watershed. This article turns to frame the structural elements and specific actions that, contrary to the pluralist view, prevented Spanish elites from supplying a political solution to a fundamentally political problem and, in turn, helped trigger the crisis. By situating the political clash in contentious politics, we observe how elite-led depoliticization unfolded in three manners: damaging institutional legitimacy; politicizing justice and finally framing the conflict in media towards repression. Departing from Scott's description of the interrelationship between power, rule and resistance, some conclusions follow to help shed light onto the current debate around the role of elites in similar 'democratic failures.'